Distribution and Evolution of the Xylanase Genes xynA and xynB and Their Homologues in Strains of Butyrivibrio fibrisolvens - Dalrymple, Brian P. (American Society for Microbiology, 1999)
The ruminal bacterium Butyrivibrio fibrisolvens is being engineered by the introduction of heterologous xylanase genes in an attempt to improve the utilization of plant material in ruminants. However, relatively little is known about the diversity and distribution of the native xylanase genes in strains of B. fibrisolvens. In order to identify the most appropriate hosts for such modifications, the xylanase genotypes of 28 strains from the three 16S ribosomal DNA (rDNA) subgroups of Butyrivibrio fibrisolvens have been investigated. Only 4 of the 20 strains from 16S rDNA group 2 contained homologues of the strain Bu49 xynA gene. However, these four xynA-containing strains, and two other group 2 strains, contained members of a second xylanase gene family clearly related to xynA (subfamily I). Homologues of xynB, a second previously described xylanase gene from B. fibrisolvens, were identified only in three of the seven group 1 strains and not in the group 2 and 3 strains. However, six of the group 1 strains contained one or more members of the two subfamilies of homologues of xynA. The distribution of genes and the nucleotide sequence relationships between the members of the two xynA subfamilies are consistent with the progenitor of all strains of B. fibrisolvens having contained a xynA subfamily I gene. Since many xylanolytic strains of B. fibrisolvens did not contain members of either of the xynA subfamilies or of the xynB family, at least one additional xylanase gene family remains to be identified in B. fibrisolvens.